Adoption of balanced scorecard and non-financial performance of tertiary institutions in Nigeria / Oyerogba Ezekiel Oluwagbemiga and Adekola Omotayo Ajibike - Oluwagbemiga, Oyerogba Ezekiel; Ajibike, Adekola Omotayo (Universiti Teknologi MARA, 2021)
The gap existing in the developing countries on whether adoption of BSC a significant influence on non-financial performance of tertiary institutions in Nigeria has using employers' rating as a measure of performance, necessitated this study. The study used a survey research design. The population of the study consisted of all the sixty-eight (68) tertiary institutions in South Western Nigeria which comprised publicly and privately owned universities and polytechnics where a sample of 34 institutions were drawn using the multistage sampling technique. Data was collected using a five-point likert scale questionnaire from 209 respondents purposively drawn from the various categories of staff of the institutions selected. Data were analyzed using descriptive and inferential statistics. The results revealed that there is a significant improvement in the performance of tertiary institutions in Nigeria after adoption of the balanced scorecard. Also, we reported that about 63% of the variation in the ways in which graduates of Nigerian institutions are rated by the employers are associated with the combined effects of all the four components of the balanced scorecard investigated in this study. This research concluded that the balanced scorecard has a significant positive effect on the performance of tertiary institutions in Nigeria.